P0116 Updated clinical efficacy of the anti-PD-1 monoclonal antibody pembrolizumab (MK-3475) in 411 patients with melanoma. (July 2015) - Ribas, A.; Wolchok, J.D.; Robert, C.; Kefford, R.; Hamid, O.; Daud, A.; Hwu, W-J.; Weber, J.S.; Joshua, A.M.; Gangadhar, T.C.; Patnaik, A.; Hersey, P.; et al.
Abstract : Background: Pembrolizumab is a potent humanised monoclonal antibody against PD-1 that has shown efficacy and safety in patients with advanced solid tumours and haematological malignancies. Methods: KEYNOTE-001 (NCT01295827) was a multicohort phase 1 study that included 411 patients with advanced melanoma, including 221 who previously received ipilimumab (IPI-T) and 190 who were ipilimumab naive (IPI-N). Patients received pembrolizumab at 10 mg/kg every 3 weeks (Q3W), 2 mg/kg Q3W, or 10 mg/kg Q2W. Response was assessed every 12 weeks per RECIST v1.1 by independent central review and per immune-related response criteria (irRC) by the investigator. Findings: As of the April 18 2014, median follow-up duration for all patients was 18 months (range 12–28). The 360 patients with measurable disease per central review at baseline had objective response/disease control rates per RECIST of 34%/54% (29%/54% in IPI-T patients, 39%/55% in IPI-N patients). By irRC, objective response/disease control rates were 39%/64% (34%/65% in IPI-T patients, 45%/64% in IPI-N patients). 57 patients who had progressive disease by RECIST had non-progressive disease by irRC. Responses were durable, with 81% ongoing at analysis (median response duration not reached; range, 6+ to 98+ weeks). Pembrolizumab showed antitumour benefit at all doses and schedules regardless of ECOG performance status, previous IPI, or LDH levels. Per RECIST, 6-month PFS was 45% (42% for IPI-T, 48% for IPI-N). Median overall survival was 25.9 months, with a 69% 1-year overall survival (65% for IPI-T, 74% for IPI-N). Pembrolizumab was safe and well tolerated, with 14% of all patients experiencing drug-related grade 3/4 adverse events (15% IPI-N, 14% IPI-T) and only 5% discontinuing pembrolizumab because of a drug-related adverse events (6% IPI-N, 5% IPI-T). There were no treatment-related deaths. Interpretation: Pembrolizumab provides a favourable benefit-risk profile in both IPI-T and IPI-N patients, suggesting it could be a promising treatment option for all patients with advanced melanoma.